2014
DOI: 10.1088/0957-0233/25/6/065701
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive technique for assessment of vascular wall stiffness using laser Doppler vibrometry

Abstract: It has been shown that in cardiovascular risk management, stiffness of large arteries has a very good predictive value for cardiovascular disease and mortality. This parameter is best known when estimated from the pulse wave velocity (PWV) measured between the common carotid artery (CCA) in the neck and femoral artery in the groin, but may also be determined locally from short-distance measurements on a short vessel segment. In this work, we propose a novel, non-invasive, non-contact laser Doppler vibrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Yanlu Li et al suggested a system with two laser Doppler vibrometry as a potential technique to measure the local carotid PWV in two locations along the common carotid artery from skin vibrations [ 69 ]. Recently, Adriaan Campo et al presented an instrument with a double laser Doppler vibrometer to assess the local PWV at the carotid site [ 70 ].…”
Section: Devicesmentioning
confidence: 99%
“…Yanlu Li et al suggested a system with two laser Doppler vibrometry as a potential technique to measure the local carotid PWV in two locations along the common carotid artery from skin vibrations [ 69 ]. Recently, Adriaan Campo et al presented an instrument with a double laser Doppler vibrometer to assess the local PWV at the carotid site [ 70 ].…”
Section: Devicesmentioning
confidence: 99%
“…Therefore, it is possible to detect the pulse wave at multiple known locations along the trajectory of the vessel and to calculate the PWV. Previous experiments indicate that LDV can be used to measure cfPWV and local carotid PWV [10], [11]. In this study, we assess the feasibility of the 4-channel vibrometer system to assess PWV velocity of phantoms with varying architectural traits, mimicking gross arterial pathologies.…”
Section: Local Pulse Wave Velocity Detectionmentioning
confidence: 99%
“…Heart periods are computed from the R peaks of the ECG and the corresponding peaks in the LDV, which are identified by means of a semi-automatic algorithm based on [ 29 ]. Other researchers (e.g., [ 23 , 30 , 31 , 32 , 33 ]) focus on estimating the pulse-wave velocity, which measures the speed of propagation of pulse waves along the arterial tree. In this work, the analysis still relies on manual intervention and/or ECG signal availability.…”
Section: Introductionmentioning
confidence: 99%